Current Status of Vascularized Composite Allotransplantation. Issue 6 (June 2019) - Kaufman, Christina L.; Bhutiani, Neal; Ramirez, Allan; Tien, Huey Y.; Palazzo, Michelle D.; Galvis, Elkin; Farner, Scott; Ozyurekoglu, Tuna; Jones, Christopher M.
The field of vascularized composite allotransplantation (VCA) has moved from a highly experimental procedure to, at least for some patients, one of the best treatment alternatives for catastrophic tissue loss or dysfunction. Although the worldwide experience is still limited, progress has been made in translation to the clinic, and hand transplantation was recently designated standard of care and is now covered in full by the British Health System. This progress is tempered by the long-term challenges of systemic immunosuppression, and the rapidly evolving indications for VCA such as urogenital transplantation. This update will cover the state of and recent changes in the field, and an update of the Louisville VCA program as our initial recipient, the first person to receive a hand transplant in the United States celebrates the 20th anniversary of his transplant. The achievements and complications encountered over the last two decades will be reviewed. In addition, potential directions for research and collaboration as well as practical issues of how third party payers and funding are affecting growth of the field are presented.